2014
DOI: 10.1210/en.2013-2105
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of PPARγ-Regulated MicroRNAs in Human Subcutaneous and Visceral Adipogenesis in both Genders

Abstract: Clinical evidence shows that visceral fat accumulation decreases whereas sc fat increases in patients treated with thiazolidinediones (TZDs), a type of peroxisome proliferator-activated receptor (PPAR)γ agonist. To clarify the molecular mechanism of the differential effects of PPARγ agonists on sc and visceral adipose, we investigated expression profiling of PPARγ-regulated micro-RNAs (miRNAs) using miRNA microarray. The level of 182 miRNAs changed in human sc adipose treated with pioglitazone, whereas only 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 34 publications
1
31
1
Order By: Relevance
“…Apparently, stable high expression level of miR-378 is required for CRC cells response to Cetuximab, irrespective of their BRAF or KRAS status (Fig. 4a, Table I) (24). We noted a contradictory effect on the cell survival between BRAF and KRAS mutated CRC cells after performing miR-378 transfection in vitro.…”
Section: Discussionmentioning
confidence: 70%
“…Apparently, stable high expression level of miR-378 is required for CRC cells response to Cetuximab, irrespective of their BRAF or KRAS status (Fig. 4a, Table I) (24). We noted a contradictory effect on the cell survival between BRAF and KRAS mutated CRC cells after performing miR-378 transfection in vitro.…”
Section: Discussionmentioning
confidence: 70%
“…Studies have suggested that several miRNAs play a role in adipose tissue development and associated metabolism (155). A study used miRNA microarray analysis to profile PPAR␥-regulated miRNAs in human adipocytes (156). Among 27 miRNAs whose expression was altered by treatment of pioglitazone, a synthetic PPAR␥ ligand, miR-378, has been shown to promote adipogenesis of subcutaneous adipocytes but not of visceral adipocytes.…”
Section: Epigenomic Regulation Of Adipogenesismentioning
confidence: 99%
“…Accordingly, the exposure of adipocytes to thiazolidinediones, a fat-cell differentiation driver, resulted in the over-expression of around 200 miRNAs in subcutaneous adipocytes, whereas only a small number of these miRNAs were found to be expressed in visceral-derived adipocytes (Yu et al, 2014). Furthermore, regional differences in levels of miRNA expression within subcutaneous white adipose tissue have also been described (Rantalainen et al, 2011).…”
Section: Mirna and Obesitymentioning
confidence: 99%